Communities’ Adaptation and Vulnerability to Climate Change: Implications for Achieving a Climate-Smart Landscape - Widayati, Atiek; Louman, Bastiaan; Mulyoutami, Elok; Purwanto, Edi; Kusters, Koen; Zagt, Roderick (Land (Basel), 2021)
Rural landscapes in many parts of Indonesia are rapidly being transformed, due to the expansion of agrocommodity plantations—oil palm in particular. At the same time, communities in those landscapes face declining crop yields and ecosystem degradation as a result of both climate and non-climate factors. We assessed local perceptions on climate stressors, adaptation and vulnerability using focus group discussions in Ketapang, West Kalimantan. We found that the main perceived climatic stressors were extreme and unpredictable seasons, fires, and saltwater intrusion, affecting ecosystem services and agricultural production. Land clearing and forest loss were mentioned as exacerbating non-climatic stressors. Respondents indicated willingness to adapt to these changes by investing in long-term measures, such as tree-planting. To adapt to yield declines, respondents indicated that many farmers shifted from rubber to oil palm. Such adaptation actions benefit households in the short term but may be at odds with long-term adaptation objectives at the landscape level. Finally, we found that perceptions about vulnerability differed between landscapes, and between communities at the landscape level and stakeholders at the district level. This stresses the importance of participatory and inclusive planning and multi-stakeholder processes towards context-based climate action planning to accommodate the differences in contexts and scale, and to reconcile the differences in perceptions.